Anthropology and Public Health 2009
DOI: 10.1093/acprof:oso/9780195374643.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

Indigenization of Illness Support Groups for Lymphatic Filariasis in Haiti

Abstract: This chapter describes the process of indigenization within peer support groups for Haitian women living with the physical impairment of lymphatic filariasis. The groups developed a distinctive style characterized by minimal interest in talking about the illness and a strong interest in religion and spirituality, artistic and expressive components, acquisition of practical skills, and microenterprise activities. The context of indigenous traditions of mutual aid, material needs of families, and political and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The important feature of this study is that 91% had to average to good quality of life and it has association with self help group involvement. Same finding was reported by Coreil J et al 10 .His study reported that support groups offer a low cost ,psychosocial intervention for people living with chronic diseases and disability 11 . The Study has the following limitations.…”
Section: Discussionsupporting
confidence: 61%
“…The important feature of this study is that 91% had to average to good quality of life and it has association with self help group involvement. Same finding was reported by Coreil J et al 10 .His study reported that support groups offer a low cost ,psychosocial intervention for people living with chronic diseases and disability 11 . The Study has the following limitations.…”
Section: Discussionsupporting
confidence: 61%
“…The relative contribution of each component of the overall intervention is unclear; we believe that they acted synergistically. Coreil and colleagues showed that patients in Leogane who regularly participated in support groups had a lower incidence of ADLA than those who did not [30] . In addition, self-efficacy (belief in one's ability to perform lymphedema self-care) increased significantly following distribution of booklets and broadcasts of the radio dramas (Wendt, JM, unpublished thesis, Emory University, Atlanta, GA).…”
Section: Discussionmentioning
confidence: 99%
“…These were often dramatic. Patients commonly reported decreased stigma and shame and a return to active life, including school or work [30, Wendt JM, unpublished] . Those with advanced lymphedema and multiple skin folds and lesions reported, often for the first time in years, the elimination of offensive odor.…”
Section: Discussionmentioning
confidence: 99%
“…Participation in patient support groups has been shown to decrease the number of ADLA episodes and improve quality of life among lymphoedema patients in Haiti [81]. …”
Section: Acute Inflammatory Episodes (Acute Attacks)mentioning
confidence: 99%
“…Participation in patient support groups was shown to decrease the number of ADLA episodes and improve quality of life among lymphoedema patients in Haiti [81]. In Brazil, patient 'Hope Clubs' have been developed to provide ongoing opportunities for social and emotional support, problem-solving, and continued learning [124].…”
Section: Lymphoedemamentioning
confidence: 99%